PERANCANGAN FASILITAS PRODUKSI TAHU YANG ERGONOMIS PADA IKM TAHU PAK SARNO - Hardianto, Risky; Zetli, Sri (Computer Science and Industrial Engineering, 2026)
Pak Sarno Tofu Factory is a small and medium enterprise (SME) in Batam City that stillapplies a semi-manual work system, particularly in the tofu whey sedimentation process.The manual scooping and handling of tofu whey using ladles and buckets potentially causemusculoskeletal complaints and reduce work efficiency. This study aims to identify the levelof Musculoskeletal Disorders (MSDs) using the Nordic Body Map (NBM), analyze workposture risk using the Rapid Entire Body Assessment (REBA) method, and design anergonomic work facility using the Ergonomic Function Deployment (EFD) method. Theresults indicate that workers experience musculoskeletal complaints in the neck, shoulders,lower back, waist, arms, wrists, and lower limbs, with the highest complaint level occurringin activities classified as high risk. REBA analysis shows that ergonomic risk levels rangefrom moderate to high, with the highest REBA score of 9 occurring during the activity ofcarrying buckets filled with tofu whey, which is classified as a high-risk activity. Based on theEFD method, an ergonomic sedimentation tool was designed in the form of a 250-literstainless steel drum equipped with a faucet system, a roller-supported table, and dimensionsadjusted to workers’ anthropometry. This design is expected to reduce physical workload,minimize MSDs complaints, and improve production efficiency.